How Effective is FYP (ForYouPage) Campaign for Business Contents on in Indonesia? - Adha Faubya Hasanah; Liza Agustina Maureen Nelloh; Sasotya Pratama (Indonesia Banking School, 2022)
TikTok has gaining popularity in Indonesia recently and many of the businesses in Indonesia use this platform to communicate their value proposition. Hence, the previous studies about Technology of Acceptance Model has been tested in many settings, but still limited to this effectiveness of the platform especially the campaign of ForYouPage (FYP) for business contents in Indonesia. Some evident shows that in some business contents, customers find it low engagement and interaction between company and users. Therefore, In order to test the effectiveness of FYP business content in Indonesia, we applied purchase intention from users in the perspectives of perceived usefulness and perceived playfulness. The questionnaires have been distributed to 100 TikTok users all over Indonesia. The method of analysis is SEM-PLS with SmartPLS v3.27 to test the hypotheses. The results show that perceived usefulness and perceived playfulness are significant to increase purchase intention of FYP business contents. This study recommends the business entities to explore more about the short video contents to be more engaging, entertaining, eye-catching, and educating to create more purchase intention among users of FYP business contents.